(untitled) (Medico Legal Update, 2020)
Posyandu is one form of Community-Based Health Efforts held together with the community in obtaining basic health services. The cadre’s role is to provide health information to the community, as a community mobilizer to come to Posyandu and a motivator to realize maternal and child health. The research was aimed at developing an effort to improve the performance of Posyandu cadres based on an analysis of empowerment in Tulungagung Regency. The study was conducted using observational analytic method with a sample of 32 Posyandu. The study was conducted in Tulungagung Regency in January-March 2020. The results showed that there was a relationship between the process of empowering and capability empowerment with the performance of Posyandu cadres (0.019; 0.001). There was a relationship between cadre training and alignment (0.002); the relationship between the availability of facilities and the role of the village with capability (0.042; 0.028) and the relationship between the development of cadres and trusts (0.028). It could be concluded that the performance of Posyandu cadres was influenced by the process of empowering alignment and capability. While trust was not related to the performance of Posyandu cadres. The process of empowering alignment was influenced by cadre training; capability was influenced by the availability of facilities and the role of villages.